2003
DOI: 10.1161/01.cir.0000055737.15443.f8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal and Humoral Properties of a Novel Direct Soluble Guanylate Cyclase Stimulator BAY 41-2272 in Experimental Congestive Heart Failure

Abstract: Background-BAY 41-2272 is a recently introduced novel orally available agent that directly stimulates soluble guanylate cyclase (sGC) and sensitizes it to its physiological stimulator, nitric oxide. To date, its therapeutic actions in congestive heart failure (CHF) remain undefined. We characterized the cardiorenal actions of intravenous BAY 41-2272 in a canine model of CHF and compared it to nitroglycerin (NTG). Methods and Results-CHF was induced by rapid ventricular pacing for 10 days. Cardiorenal and humor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 12 publications
4
65
0
3
Order By: Relevance
“…24 Most of the actions of natriuretic peptides, including the suppression of cardiac hypertrophy and fibrosis, are assumed to be mediated by intracellular cGMP. It has been shown that the direct sGC stimulator BAY41-2272 also exerts its effects by raising intracellular cGMP levels, [15][16][17] and consistent with this, BAY41-2272 increased cGMP levels in the LV myocardium tissue and in cultured cardiac fibroblasts in the present study. Because a question may arise over activity of the natriuretic peptide particulate GC system during activation of sGC by BAY41-2272, we measured plasma ANP and BNP levels in the study groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…24 Most of the actions of natriuretic peptides, including the suppression of cardiac hypertrophy and fibrosis, are assumed to be mediated by intracellular cGMP. It has been shown that the direct sGC stimulator BAY41-2272 also exerts its effects by raising intracellular cGMP levels, [15][16][17] and consistent with this, BAY41-2272 increased cGMP levels in the LV myocardium tissue and in cultured cardiac fibroblasts in the present study. Because a question may arise over activity of the natriuretic peptide particulate GC system during activation of sGC by BAY41-2272, we measured plasma ANP and BNP levels in the study groups.…”
Section: Discussionsupporting
confidence: 90%
“…22,23 Accordingly, not simply controlling systemic blood pressure but also pharmacological approaches to managing cardiovascular remodeling are necessary for treatment of hypertensive patients. The direct sGC stimulator BAY41-2272 has been shown to lower arterial pressure and peripheral resistance and to increase cardiac output and renal blood flow by raising intracellular cGMP levels [15][16][17] ; however, it remained to be elucidated whether this compound affects cardiac remodeling. In the present study, the continuous stimulation of sGC with BAY41-2272 attenuated LV hypertrophy and fibrosis in rats with Ang II-induced hypertension, suppressing the phenotypic change of fibroblasts and the expression of extracellular matrix-related genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 We and others have shown the beneficial effects of this compound not only on hemodynamics, but also on cardiovascular remodeling. [15][16][17][18] As sGC/cGMP activation has been shown to interfere with RAS, 19,20 we tested the hypothesis that the direct stimulation of sGC with BAY 41-2272 could attenuate myocardial fibrosis by inhibiting RAS activation. In this study, we used rats with pressure overload induced by suprarenal aortic constriction (AC), a model of hypertensive heart disease accompanied by fibroblast and RAS activation.…”
Section: Introductionmentioning
confidence: 99%
“…This is considered to be the primary mechanism through which it produces antiplatelet activity, a strong decrease in blood pressure, and increase in survival, indicating its potential for the treatment of cardiovascular disorders . Recently, several investigators have reported that BAY 41-2272 is a potent pulmonary vasodilator in different animal models of pulmonary hypertension (canine model, Boerrigter et al, 2003;awake lambs, Evgenov et al, 2004; and ovine fetus, Deruelle et al, 2005). Since the mechanism of pulmonary artery dilation by BAY 41-2272 is unclear, we used isolated ovine pulmonary artery as a model to elucidate its mechanism of relaxation.…”
mentioning
confidence: 99%